2002
DOI: 10.1016/s0304-3959(02)00028-3
|View full text |Cite
|
Sign up to set email alerts
|

Continual systemic infusion of lidocaine provides analgesia in an animal model of neuropathic pain

Abstract: We examined whether continual constant-rate infusion of lidocaine would provide analgesia during the initial post-injury phase in the chronic constriction injury model of neuropathic pain. Male Sprague-Dawley rats were divided into control and ligated groups and infused with saline or lidocaine (0.15, 0.33, 0.67, and 1.3mg/kg/h) via subcutaneously implanted Alzet((R)) osmotic minipumps. Thermal withdrawal latencies were obtained prior (Day 0) and 3 days after loose sciatic ligation and pump implantation surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…This finding on the failure of a single pre-emptive treatment was similar to our previous study in which we also found that only continual, rather than single, application of lidocaine was effective in abolishing pain behavior 7 days after loose ligation of the sciatic nerve (Smith et al, 2002).…”
Section: The Levels Of Kcc2 Protein In the Dorsal Horn Recovered 7 Dasupporting
confidence: 90%
“…This finding on the failure of a single pre-emptive treatment was similar to our previous study in which we also found that only continual, rather than single, application of lidocaine was effective in abolishing pain behavior 7 days after loose ligation of the sciatic nerve (Smith et al, 2002).…”
Section: The Levels Of Kcc2 Protein In the Dorsal Horn Recovered 7 Dasupporting
confidence: 90%
“…Several studies have reported that systemic administration of lidocaine decreases ectopic activity recorded from injured peripheral sensory fibers (Chabal et al, 1989;Devor et al,1992;Omana-Zapata et al,1997a;Sotgiu et al, 1992) and reduces neuropathic pain (Brochu et al, 2006;Erichsen et al, 2003;Sinnott et al, 1999;Smith et al, 2002). Furthermore, systematic reviews of human studies using systemic administration of local anesthetic drugs support their use for neuropathic pain (Kalso et al, 1998) and, in addition, topical or local administration of antidepressants (Lynch et al, 2005;McCleane, 2000) and local anesthetics (Abram, 2000;Galer et al, 1999;Galer, 2002;Galer et al, 2002;Herrmann et al, 2005;Khaliq et al, 2007;Koltzenburg et al, 1994;Meier et al, 2003;Nystrom and Hagbarth, 1981;Roganovic and Mandic-Gajic, 2006;Rowbotham et al, 1996;Varrassi et al, 2006;Vranken et al, 2002) have been demonstrated to be effective in treating neuropathic pain in controlled clinical trials.…”
Section: Contribution Of Peripheral Drive To Spontaneous Activity Of mentioning
confidence: 99%
“…)-channel blockade, probably due to their pharmacological properties. Although the underlying mechanisms of this persistent analgesic effect are largely unknown, several hypotheses have been proposed: interrupting nociceptor activity with local anesthetics not only leads to reversible sensitization of spinal-cord neurons but might also induce plastic changes in neurons depending on the timing and period of exposure [5][6][7]. Identifying the mechanisms of action of local anesthetics to relieve chronic pain might lead to the development of a new strategy to treat neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%